No more ‘business as usual’ with audit and feedback interventions: towards an agenda for a reinvigorated intervention - Ivers, Noah M; Sales, Anne; Colquhoun, Heather; Michie, Susan; Foy, Robbie; Francis, Jill J; Grimshaw, Jeremy M (Implementation science : IS, 2014)
Background Audit and feedback interventions in healthcare have been found to be effective, but there has been little progress with respect to understanding their mechanisms of action or identifying their key ‘active ingredients.’ Discussion Given the increasing use of audit and feedback to improve quality of care, it is imperative to focus further research on understanding how and when it works best. In this paper, we argue that continuing the ‘business as usual’ approach to evaluating two-arm trials of audit and feedback interventions against usual care for common problems and settings is unlikely to contribute new generalizable findings. Future audit and feedback trials should incorporate evidence- and theory-based best practices, and address known gaps in the literature. Summary We offer an agenda for high-priority research topics for implementation researchers that focuses on reviewing best practices for designing audit and feedback interventions to optimize effectiveness.